2020
DOI: 10.1302/1863-2548.14.190126
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo paralysis of the shoulder and increased C-reactive protein are predictive factors for septic shoulder in children superior to other clinical symptoms: A retrospective case series of 25 patients

Abstract: Purpose The aim of the study was to evaluate predictable parameters with the highest sensitivity used in the diagnosis of children septic shoulder arthritis. Methods All children treated in our paediatric orthopaedic hospital between 2000 and 2017 with intraoperative verified septic arthritis of the shoulder were included in this retrospective study. Diagnostic procedures e.g. ultrasound, MRI, radiograph or blood samples as well as typical clinical symptoms were evaluated as predictable parameters for septic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…Schmidt et al 14 described septic arthritis of the shoulder as a “disease of infancy,” as 8 of the 9 patients in their series were under 18 months of age. Similarly, Danilov et al 6 evaluated 25 patients with septic arthritis of the shoulder and half of their cohort was between 4 weeks and 3 years of age, which is consistent with our findings. It is unclear why infants and very young children are more susceptible to septic arthritis of the shoulder.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Schmidt et al 14 described septic arthritis of the shoulder as a “disease of infancy,” as 8 of the 9 patients in their series were under 18 months of age. Similarly, Danilov et al 6 evaluated 25 patients with septic arthritis of the shoulder and half of their cohort was between 4 weeks and 3 years of age, which is consistent with our findings. It is unclear why infants and very young children are more susceptible to septic arthritis of the shoulder.…”
Section: Discussionsupporting
confidence: 91%
“…It is unclear why infants and very young children are more susceptible to septic arthritis of the shoulder. Interestingly, two-thirds of the intraoperative cultures in Danilov et al ’s6 series were negative. Of the patients who had positive cultures, Staphylococcus aureus and group B Beta-hemolytic Streptococcus were the most common.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This initiated further evaluation with serologic studies which revealed elevated inflammatory markers leading to prompt advanced imaging and surgical intervention. A recent retrospective case series by Danilov et al ( 9) examined predictive factors for the diagnosis of septic arthritis in pediatric patients and found the two most reliable factors to be pseudo paralysis and elevated CRP, both of which were present in our patient and support this algorithm of evaluation (9). Other studies found similar findings with patients often having joint pain, fever, and elevated inflammatory markers (10,11).…”
Section: Discussionsupporting
confidence: 81%